DETERMINANTS OF REGIONAL DEVELOPMENT BANK PERFORMANCE WITH OPERATIONAL EFFICIENCY AS AN INTERVENING VARIABLE - Julis Santosa; Wiwik Lestari (Universitas Nusa Cendana, 2026)
This study investigates the effects of capital adequacy, liquidity, and credit risk on the financial performance of conventional Regional Development Banks (RDBs) in Indonesia, with operational efficiency examined as a mediating variable. Capital adequacy, liquidity, and credit risk are proxied by the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non-Performing Loan (NPL) ratio, respectively, while operational efficiency and financial performance are measured using the Operating Expenses to Operating Income ratio (BOPO) and Return on Assets (ROA). The study utilizes secondary data derived from the financial statements of 24 conventional RDBs over the 2019–2024 period, generating panel observations for analysis. Panel data regression with a Random Effects Model is employed, and the mediating role of operational efficiency is examined using the Sobel test. The findings reveal that capital adequacy and liquidity exert positive but insignificant effects on financial performance, whereas credit risk has a significant negative effect. Operational efficiency does not mediate the relationship between capital adequacy and liquidity and financial performance but significantly mediates the effect of credit risk on financial performance. These results underscore the importance of effective credit risk management and cost efficiency in enhancing bank profitability and ensuring sustainable financial performance. Keywords: Performance; Capital Adequacy; Liquidity; Credit Risk; Operational Efficiency